2019
DOI: 10.3389/fncir.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Specific Adaptation Decreases the Coupling of Spikes to LFP Phase

Abstract: Stimulus repetition suppresses the neural activity in different sensory areas of the brain. This mechanism of so-called stimulus-specific adaptation (SSA) has been observed in both spiking activity and local field potential (LFP) responses. However, much remains to be known about the effect of SSA on the spike–LFP relation. In this study, we approached this issue by investigating the spike-phase coupling (SPC) in control and adapting paradigms. For the control paradigm, pure tones were presented in a random un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The main purposes of this study were to (i) evaluate the potential of the tone frequency tuning curve (sensory information) based on SPC, and (ii) examine the effect of adaptation on this tuning curve. In a recent study, we showed that SSA reduces the SPC strength significantly in the beta range (Parto Dezfouli et al, 2019). Resembling previous procedure, in this work, we analyzed the power of SPC in terms of tuning curve for sensory information coding.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The main purposes of this study were to (i) evaluate the potential of the tone frequency tuning curve (sensory information) based on SPC, and (ii) examine the effect of adaptation on this tuning curve. In a recent study, we showed that SSA reduces the SPC strength significantly in the beta range (Parto Dezfouli et al, 2019). Resembling previous procedure, in this work, we analyzed the power of SPC in terms of tuning curve for sensory information coding.…”
Section: Discussionmentioning
confidence: 85%
“…To this end, we divided LFP to six canonical frequency bands, namely delta, theta, alpha, beta, low and high gamma. Results indicated a significant difference in the SPC values between control and adaptation conditions within the beta range, but not in other bands (Parto Dezfouli et al, 2019). Therefore, here, we focused our analyses within the beta range (13-30 Hz).…”
Section: Sensory Representation Based On Spike-lfp Couplingmentioning
confidence: 96%
See 2 more Smart Citations
“…We attempted to replicate as closely as possible the in vivo experimental protocols used to explore SSA in rodent auditory cortex 4,5,13,14,29,35,67 . To achieve this, two tones f1 = 6,666 Hz and f2 = 9,600 Hz were selected as the base frequencies for our simulations; these frequencies are separated by 0.52 octaves around the center frequency of the simulated cortical circuit (8,000 Hz); see Fig.…”
Section: Ssa Protocolsmentioning
confidence: 99%